Trois places pour le 26 - Legrand, Michel 1932-2019 (Arte Vidéo [u.a.], 2008)
Yves Montand plays himself in this musical. He arrives in Marseilles by train to film his autobiography but in his spare time searches for his first love Mylène who is already married and has a daughter who dreams of starring in a musical. The film is seen as a retrospective on Demy's life and also Montand's
Orig.: F 1988. - Originally released as a motion picture in 1988
Bildformat 16:9, 4:3. - Filmlaufzeit 98 Min.
Enth. a critique of the film by Agnès Varda, Rosalie Varda and Mathieu Demy ; Mathieu Demy reads from a book by Jean-Pierre Berthomé ; featurette: Jacques Demy ou L'arbre gémeau ; photo gallery ; Archive Ina: Emission L'art en tête (1987) portrait de Jacques Demy
Keywords: Motion pictures / France; Film; Motion pictures -- France; Frankreich; Feature films; Musical films; Short films